Kristalisasi Butir Pancasila sebagai Fondasi Hukum Budaya di Republik Indonesia - Maria Yeti Andrias; Zonita Zirhani Rumalean (LPPM Universitas Ekasakti Padang, 2023)
This paper aims to deepen the understanding of the Pancasila concept as a legal source within the context of national culture in the framework of the unitary state of the Republic of Indonesia. The research employs a documentary literature review approach. The analysis results conclude that